Unleashing Translational Opportunities of Loco-Regional Drug Delivery to Treat Malignancy - Sachan, Pranjal; Shrivastava, Prachi; Goswami, Meenakshi (Asian Pacific Journal of Cancer Biology, 2025)
Background: Loco-regional drug delivery for cancer treatment has emerged as a promising approach to enhance therapeutic efficacy while minimizing systemic toxicity. Various strategies have been developed, including localized drug delivery systems and targeted delivery methods, to improve drug distribution and retention at tumor sites. Despite significant progress, several challenges persist, necessitating further exploration and innovation. Objective: This review aims to provide insights into the recent advances and challenges in loco-regional drug delivery for cancer therapy and identify future translational opportunities in this field. Materials and Methods: A literature search was conducted on loco-regional drug delivery systems for cancer treatment, identifying advancements in nanoparticle-based formulations, hydrogels, implants, and image-guided delivery techniques. Challenges include drug resistance, limited tumor tissue penetration, and tumor microenvironment complexity. Conclusion: Loco-regional drug delivery has the potential to transform cancer therapy by allowing for precision targeting, combining therapeutic modalities, using nanotechnology, and utilising modern imaging tools. Discussion: Collaboration among academics, physicians, and industry stakeholders is critical for expediting the clinical translation of innovative drug delivery platforms, which have the potential to drastically improve malignancy patient outcomes as well as enable personalised treatment methods.